METHODOLOGY FOR THE FORMATION OF THE LEGAL CULTURE OF CHILDREN OF PRESCHOOL AGE - Muminova Gulasal Bakhodirovna; Abdurahimova Munisa (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article highlights the modern mechanisms of pedagogical education, which are aimed at increasing the legal culture of schoolchildren. Also in the upbringing of the child as an active citizen of society, the caregivers of the preschool organization and the functions of the parents in the family were analyzed in a scientific-theoretical and practical way.